2019
DOI: 10.1038/s41587-019-0331-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, continuous mutagenesis in human cells using a pseudo-random DNA editor

Abstract: Here we describe TRACE (T7 polymerase-driven continuous editing), a method that enables continuous, targeted mutagenesis in human cells using a cytidine deaminase fused to T7 RNA polymerase. TRACE induces high rates of mutagenesis over multiple cell generations in genes Reprints and permissions information is available at www.nature.com/reprints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 27 publications
(33 reference statements)
0
82
0
Order By: Relevance
“…By placing the P T7 at the 3′-end of the target gene, in reverse orientation, expression of the target gene can be preserved from its endogenous 5′-promoter recognized by the host RNAP. Two recent independent studies have also reported the mutagenic activity of CD fusions to T7RNAP, in E. coli 21 and in mammalian cells 22 . Moore et al 21 described a chimeric fusion between rAPOBEC1 and T7RNAP (MutaT7) that in E. coli introduces mutations within a plasmid DNA segment downstream of P T7 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…By placing the P T7 at the 3′-end of the target gene, in reverse orientation, expression of the target gene can be preserved from its endogenous 5′-promoter recognized by the host RNAP. Two recent independent studies have also reported the mutagenic activity of CD fusions to T7RNAP, in E. coli 21 and in mammalian cells 22 . Moore et al 21 described a chimeric fusion between rAPOBEC1 and T7RNAP (MutaT7) that in E. coli introduces mutations within a plasmid DNA segment downstream of P T7 .…”
Section: Introductionmentioning
confidence: 93%
“…The study in mammalian cells uses fusions of rAPOBEC1 or a hyperactive mutant AID to T7RNAP. Mutations in a DNA segment of at least 2000 bp were reported, but no brake system was included to delimit the edited window 22 . In this work, we describe the mutagenic action of different BDs (i.e., AID, rAPOBEC1, pmCDA1, and TadA*) fused to T7RNAP on a target genomic DNA segment in E. coli chromosome.…”
Section: Introductionmentioning
confidence: 99%
“…Although indels are applicable to regulatory regions and even coding sequences [55][56][57] , point mutagenesis would enable fi ne mapping of regulatory nucleotides and amino acids. This exciting possibility could be opened up by implementing hyperactive base [58][59][60][61] -or prime editors [62][63][64] . Alternatives to CRISPR-Cas could be developed based on inducible expression of cassette exchange 65,66 or targeted transposons 67,68 .…”
Section: Discussionmentioning
confidence: 99%
“…Both of those limitations inherent to exploring long time scales of adaptation using barcoding approaches would likely be mitigated by using an approach that allows either periodic introduction of additional barcodes (as in 38 ), or allows modification of barcodes over time (e.g. 9 ), to maintain barcode diversity within the evolving populations, and measuring fitness of isolated clones in each of the environments at each environmental switch.…”
Section: Discussionmentioning
confidence: 99%